Strategic organisational risk management. An investigation of UK risk management practices - Robertson, Paul S. (Cranfield University, 2004)
Strategic risk management within the UK is a professional field fraught with terminological debate, a lack of academic research and a need for illustrative tools in order to improve management systems. Treating risk as a social construct, this research approached strategic organisational risk management with the aim of examining interactions currently underway within industrial practice in the UK. A thorough literature review has exposed the insufficiency of research within general risk management areas and, more specifically, the lack of research relating to strategic organisational risk management. To solve this, over 90 qualitative, in-depth interviews were conducted, amassing one of the most comprehensive collections of research material pertaining to UK risk management practice available to date. This research has enhanced the current understanding of UK risk management practice within a number of distinct areas. Firstly the terminological debate has been addressed and its vagaries to some extent dismissed. Risk managers should use this terminological resolution to bring together similar professions rather than distance them through misuse of terms. Through the interviews it has become clear that industrial events such as the Turnbull report and the events of September 11th 2001 have had very little effect upon actual risk management practices and priorities. Additionally the continuing importance of understanding context in the conduct of risk management has been emphasised. This stage of the process cannot be stressed enough. Context defines what we know, what we are capable of and the extent of the problem. Without it, all risk management processes are predestined to failure through a lack of understanding, and poor definition, of reality. A new unified model of Strategic Organisational Risk Management (STORM) has been generated which, for the first time, begins to show the levels of interactions and complexity which risk managers face at the organisational level. The STORM model further illustrates the key elements which support and divide organisational risk management practice. Identifying the deficiencies in current knowledge of strategic risk management practices, this research project has generated a tool supporting risk managers in understanding the complexities of their own organisations' risk management processes and practices. Moreover, it has created a significant starting point for future research.